Elevated microRNA-145 inhibits the development of oral squamous cell carcinoma through inactivating ERK/MAPK signaling pathway by down-regulating HOXA1. Issue 6 (25th June 2019) - Ding, Junhai; Sun, Dubin; Xie, Pengfeng
Abstract : Background: Oral cancer is one of the most frequent solid cancers worldwide, and oral squamous cell carcinoma (OSCC) constitutes approximately 90% of oral cancers. The discovery of reliable prognostic indicators would be a potential strategy for OSCC treatment. In the present study, we aim to explore the underlying mechanism by which microRNA-145 (miR-145) affected OSCC.Methods: Forty-eight patients diagnosed with OSCC were enrolled to obtain the OSCC tissues and adjacent normal tissues. The targeting relationship between miR-145 and Homeobox A1 (HOXA1) was verified . In order to assess the effects of miR-145 in OSCC and the detailed regulatory mechanism, the SCC-9 cell line was adopted, in which expression of miR-145 and HOXA1 were altered by transfection. Then, a series of in vitro and in vivo experiments were performed to evaluate the cell viability, migration, invasion, and tumor growth.Results: miR-145 was poorly expressed and HOXA1 was highly expressed in OSCC. HOXA1 was verified as a target of miR-145 to mediate the activation of the extracellular signal-regulated kinase/mitogen activated protein kinase (ERK/MAPK) signaling pathway. In the circumstance of miR-145 elevation or HOXA1 depletion, the SCC-9 cell line manifested with inhibited cell viability, invasion, and migration in vitro, coupled with reduced tumor growth in vivo, with a decreased expression of ERK/MAPK signaling pathway-related genes/proteins.Conclusion: These findings suggested that miR-145 can inhibit HOXA1 to inactivate the ERK/MAPK signaling pathway, thereby suppressing OSCC cell proliferation, migration, and invasion to further inhibit the development of OSCC, highlighting a novel therapeutic target for the OSCC treatment.